Preliminary planning efficiency evaluation for school buildings considering the tradeoffs of MOOP and planning preferences - Cheng, Min-Yuan; Chen, Ching-Shan (Journal of Civil Engineering and Management, 2014)
Seismic resistance and cost effectiveness are often two important building planning objectives for architects. However, these objectives nearly always share a negative correlation with each other, which can cause planning delays and confusion. The conflict between these two is a Multi-Objective Optimization Problem (MOOP). Besides, building planning often encompasses both subjective and objective factors. However, most current efficiency evaluation methods focus on the latter and underemphasize the former. Current efficiency evaluation methods are thus not optimized for actual building planning needs. The aim of this study is to develop a new planning efficiency evaluation approach to resolve the above problems. Research methods include the indifference curve, efficient frontier and Data Envelopment Analysis (DEA). The indifference curve deduced the subjective planning preferences of architects; efficient frontier theory constructed the efficient frontier of school buildings; and DEA evaluated the efficiency of various building factors objectively. A total of 326 school buildings in Taichung City, Taiwan in an empirical study designed to illustrate proposed approach effectiveness. The results show that using only objective evaluation or subjective recognition is insufficient to explain the true nature of building planning. Findings can serve as benchmarks for inefficient school buildings at preliminary planning stage.